Hybrid Magnetoelectric Nanowires for Nanorobotic Applications Fabrication, Magnetoelectric Coupling, and Magnetically Assisted In Vitro Targeted Drug Delivery - Chen, Xiang-Zhong (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.